I will always love you - Von Ziegesar, Cecily (New York, NY : Little, Brown and Co., 2009)
After graduating and moving on to college, Blair, Serena, Nate, Dan, and Vanessa are forced to come to terms with past events when they are reunited in the city during the holidays in this coming-of-age story.
"Poppy."
Keywords: Children of the rich -- New York (State) -- New York -- Fiction; Teenage girls. -- New York (State) -- New York -- Fiction; College students -- Fiction; New York (N.Y.) -- Fiction